Is a Pension Reform Needed in Germany? - Martin Werding (CESifo Forum, 2022)
Germany is being hit relatively hard by demographic aging. The latest round of major pension reforms dates back to the period from 2001 to 2007. The last government tried to prepare a new reform, but failed to reach a consensus. The new coalition government is not pursuing these plans any further. This article describes the changes in existing rules that the coalition is nevertheless considering and discusses actual reform needs.
Keywords: 330